Fa`āliyah Taṭbīq Uslūb Teams Games Tournament Bi Kahoot Wa aṭ-Ṭarīqah al-Qiyāsiyyah Bi al-Biṭṭāqah Li Tarqiyah Qudrah aṭ-Ṭalabah `Alā al-Qawā`id An-Naḥwiyyah (Dirāsah Tajrībiyyah Bi al-Āmiliyah Bi Ma`had al-Furqān) - Alvia Rahmi; Ahmad Fauzi (EL-MAQALAH : Journal of Arabic Language Teaching and Linguistics, 2022)
As stated by students through the interview they acknowledged the difficulties in learning Arabic such as Qawaid. Students found difficulty with the use of isim dhomir and the difference of fiil (verb) as well as the use of jar and mubtada khabar letters while learning Qawaid. Besides, they also found difficulty in formulating the correct sentences according to Qawaid rules. Based on the experience of the teacher, students’ ability is very lack in mastering the Qawaid materials. It is shown from the result of Qawaid assignments given. Furthermore, the students did not remember what the teacher explained when they were asked back by the teacher. The teacher points out that the students are lack motivation in learning Arabic. This problem will affect students' ability to accept the material. The purpose of this study was to (1) determine the effectiveness of the Teams Games Tournament model with Kahoot to improve students' ability to qawaid nahwiyyah (2) to determine the effectiveness of the Teams Games Tournament model with Kahoot to improve students' ability to qawaid nahwiyyah. (3) determine the effectiveness of the qiyasiyyah method with cards to improve students' ability to qawaid nahwiyyah. (4) knowing the effectiveness of the qiyasiyyah method with cards to improve students' ability to qawaid nahwiyyah. The research methodology in this thesis is an experimental method with a factorial design (The 2 x 2 Factorial Design). Based on the explanation, the researcher concluded that (1) The application of teams games tournament model with kahoot effective to improve the ability of students (lk) in Qawaid Nahwiyyah. With evidence that the distribution of data is at the siqnification level of 0.000 ≤ 0.05. (2) Implementation of teams games tournament model with kahhot not effective to improve the ability of students (pr) in Qawaid Nahwiyyah. With evidence that the distribution of data is at the siqnification level of 0.065 > 0.05. (3) Application of qiyasiyyah method with cards effective to improve the ability of students (lk) to Qawaid Nahwiyyah. With evidence that the distribution of data is at the siqnification level of 0.015 ≤ 0.05. (4) Application of qiyasiyyah method with cards effective to improve the ability of students (pr) in Qawaid Nahwiyyah. With evidence that the distribution of data is at the siqnification level of 0.004 ≤ 0.05.